PENGENALAN TENTANG PENGURANGAN RISIKO BENCANA GEMPA BUMI DI SMA NEGERI 10 JAKARTA: INTRODUCING EARTHQUAKE RISK REDUCTION IN SMA NEGERI 10 JAKARTA - Ilham B. Mataburu; Sony Nugratama; Warnadi (Politeknik Negeri Sriwijaya, 2022)
Policies in disaster management in Indonesia are currently more focused on disaster prevention and mitigation efforts. Strengthening disaster management capacity is a very important achievement for success in reducing the impact of disasters. Disaster impact reduction can only be done when disaster risks can be understood and identified to serve as a basis for building disaster resilience. Schools have a strategic role in relation to disaster risk reduction efforts. Classroom learning and school activities can be used as media to develop an awareness of the importance of preparedness in dealing with disasters. The introduction of disaster risk reduction as an effort to increase school resilience in dealing with earthquake disasters carried out at SMA Negeri 10 Jakarta aims to increase students' knowledge of earthquake disaster risk reduction in the school environment. The implementation method is carried out through online socialization through the Zoom program. The results of the implementation show that there is an increase in the knowledge of students and teachers on understanding earthquake risk, recognizing risk factors, and knowing how to reduce disaster risk with existing resources in the school environment. This is shown through the average results of pre-test and post-test who answered correctly increased by 44.33%. Participants who answered correctly were 79.55% from the previous 35.22%